2007
DOI: 10.3189/002214307784409199
|View full text |Cite
|
Sign up to set email alerts
|

GPS determination of the velocity and strain-rate fields on Schirmacher Glacier, central Dronning Maud Land, Antarctica

Abstract: Global positioning system (GPS) campaigns were conducted during the 2003 and 2004 austral summer seasons to obtain insight into the velocity and strain-rate distribution on Schirmacher Glacier, central Dronning Maud Land, East Antarctica. GPS data were collected at 21 sites and analyzed to estimate the site coordinates, baselines and velocities. The short-term precision of the base station, MAIT, is estimated from the daily coordinate repeatability solutions during the two years. All GPS points on the glacier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Global positioning system (GPS) campaigns were conducted during summer seasons to obtain insight into the velocity and strain-rate distribution on Schirmacher Glacier, central Dronning Maud Land, East Antarctica. GPS data were collected at 21 sites and analysed to estimate the site coordinates, baselines and velocities (Sunil et al, 2007). The velocity and strain-rate distributions across the GPS network in Schirmacher Glacier were spatially correlated with topography, subsurface undulations, fracture zones/crevasses and the partial blockage of the flow by Nunataks and the Schirmacher Oasis (Fig.…”
Section: High-resolution Satellite Data Applicationsmentioning
confidence: 99%
“…Global positioning system (GPS) campaigns were conducted during summer seasons to obtain insight into the velocity and strain-rate distribution on Schirmacher Glacier, central Dronning Maud Land, East Antarctica. GPS data were collected at 21 sites and analysed to estimate the site coordinates, baselines and velocities (Sunil et al, 2007). The velocity and strain-rate distributions across the GPS network in Schirmacher Glacier were spatially correlated with topography, subsurface undulations, fracture zones/crevasses and the partial blockage of the flow by Nunataks and the Schirmacher Oasis (Fig.…”
Section: High-resolution Satellite Data Applicationsmentioning
confidence: 99%
“…The principal strain rates provide a quantitative measurement of extension rates, which range from (0.04±0.02) x 10 -3 to (0.96±0.16) x 10 -3 a -1 . The velocity and strain rate distributions across the GPS network in Schirmacher Glacier were spatially correlated with topography, subsurface undulations, fracture zones/ crevasses and the partial blockage of the flow by nunataks and the Schirmacher Oasis (Sunil et al, 2007).…”
Section: Gps Measurements For Crustal Deformation Mass Balance and Imentioning
confidence: 99%
“…A magnetic survey of Bharati promontory was carried out to compile a magnetic anomaly map of the area (Reddy and Dhar, 2007). It is observed that the high magnetic field anomaly regions are concentrated over some pockets which are located on high ridges.…”
Section: Magnetic Anomaly Map Of Bharati Promontorymentioning
confidence: 99%
“…The principal strain rates provide a quantitative measurement of extension rates, which range from (0.11±0.01) & times 10-3 to (1.48±0.85) × 10-3 a-1, and shortening rates, which range from (0.04±0.02) × 10-3 to (0.96±0.16) × 10-3 a-1. The velocity and strain-rate distributions across the GPS network in the ice sheet, south of Schirmacher Oasis are spatially correlated with topography, subsurface undulations, fracture zones/crevasses and the partial blockage of the flow by nunataks and the Schirmacher Oasis (Sunil et al, 2007(Sunil et al, , 2010.…”
Section: Ice Sheet Dynamicsmentioning
confidence: 99%
“…The calculation of the shifting of stakes located on the Polar ice sheet with the help of hand-held GPS shows that the Polar ice sheet is moving very slowly by 2.5 m per year towards N33E, as observed in the period between 2010-11 and 2014-2015(Swain and Raghuram, 2015.…”
Section: Snow Accumulation/aablation On Ice Sheetmentioning
confidence: 99%